Emotional intelligence of parents and their reaction to a child’s speech disfluency - Humeniuk, Ewa; Tarkowski, Zbigniew; Góral-Półrola, Jolanta (Wydawnictwo Naukowe EDUsfera, 2022)
Reactions of the mothers and fathers to a child’s speech disfluency are similar, whereas the intensity of emotional reactions towards sons was statistically significantly higher (p<0.05) in the mothers than in the fathers. Both the overall level of emotional intelligence and the levels for individual scales were statistically significantly higher in the mothers (p<0.05, p<0.01, p<0.001). A positive relationship of medium strength was found between the capacity for empathy and the cognitive scale as well as between the ability to control their own emotions and the behavioural scale in the mothers. In the fathers researched in this study, a positive relationship of medium strength between the ability toempathize and the emotional scale was observed.
Keywords: stuttering; children; parents; emotional intelligence